2011
DOI: 10.5121/ijwmn.2011.3420
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison Of Topology And Position Based Routing Protocols In Vehicular Network Environments

Abstract: Due to mobility constraints and high dynamics, routing is a more challenging task in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…It also creates routing loops, which increases routing overhead. These drawbacks motivated the researchers to design a separate and an appropriate routing strategy that is suitable to overcome routing issues in the city environment [22][23][24][25][26].…”
Section: Position-based Routing In Vehicular Networkmentioning
confidence: 99%
“…It also creates routing loops, which increases routing overhead. These drawbacks motivated the researchers to design a separate and an appropriate routing strategy that is suitable to overcome routing issues in the city environment [22][23][24][25][26].…”
Section: Position-based Routing In Vehicular Networkmentioning
confidence: 99%
“…A protocol like AODV consumes additional bandwidth due to transmission of periodic heavy beacon messages in intermittently connected VANETs [14,31]. In addition, the maintenance of routing paths in highly mobile environments results in large routing overhead for topology-based routing protocols [5][6][7][8]11]. In order to overcome the restrictions of topology-based routing, position-based routing which is based on location information is introduced [35].…”
Section: Related Workmentioning
confidence: 99%
“…For the safety of drivers and regulating the flow of vehicles, the drivers have to be alerted to unwanted traffic accidents, traffic congestion, road conditions, and other associated features. The main objective of VANETs is to address these issues by providing the exact and timely information to the drivers [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the results of the collaboration of MANET and VANET showed that the performance is not that much over welcoming due to high mobility, varying speed, rapid topology changes, frequent fragmentation and high dynamic network density [13]. In literature three classes of routing protocols are listed namely reactive, proactive and geographical routing protocols [11]. Yet these approaches have their pros and cons and no single routing protocol is able to perform efficiently in all realistic scenarios.…”
Section: A Routing Protocolsmentioning
confidence: 99%